2021
DOI: 10.7554/elife.73724
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution structures of the actomyosin-V complex in three nucleotide states provide insights into the force generation mechanism

Abstract: The molecular motor myosin undergoes a series of major structural transitions during its force-producing motor cycle. The underlying mechanism and its coupling to ATP hydrolysis and actin binding is only partially understood, mostly due to sparse structural data on actin-bound states of myosin. Here, we report 26 high-resolution cryo-EM structures of the actomyosin-V complex in the strong-ADP, rigor, and a previously unseen post-rigor transition state that binds the ATP analog AppNHp. The structures reveal a h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(88 citation statements)
references
References 126 publications
(360 reference statements)
10
69
0
Order By: Relevance
“…9 ). Interestingly, the position where TcART binds to F-actin partly overlaps with the position of other F-actin interacting proteins and peptides, such as myosin-V 41 , ExoY toxin from Pseudomonas aeruginosa 42 , and the Lifeact peptide 43 , 44 . In particular, all these proteins possess a hydrophobic residue that is homologous to Y183 of TcART (M515 in myosin-V, F374 in ExoY and F10 in Lifeact).…”
Section: Discussionmentioning
confidence: 99%
“…9 ). Interestingly, the position where TcART binds to F-actin partly overlaps with the position of other F-actin interacting proteins and peptides, such as myosin-V 41 , ExoY toxin from Pseudomonas aeruginosa 42 , and the Lifeact peptide 43 , 44 . In particular, all these proteins possess a hydrophobic residue that is homologous to Y183 of TcART (M515 in myosin-V, F374 in ExoY and F10 in Lifeact).…”
Section: Discussionmentioning
confidence: 99%
“…An interaction between loop 4 and actin is supported by both cryo-EM and computational work, where evidence suggests that residue R369 is critical to this interface. Cryo-EM structures of skeletal muscle myosin II [ 24 ] and myosin V [ 27 ] bound to F-actin show direct electrostatic interactions between loop 4 and actin, though loop 4 of myosin V localizes closer towards the cardiomyopathy loop where it forms an intramolecular hydrogen bond. A molecular dynamics simulation [ 7 ] of a cryo-EM structure of actomyosin [ 21 ] incorporating the myosin II [ 28 ] and myosin V [ 29 ] crystal structures, revealed that the residue homologous to β-cardiac myosin R369 (R371) forms an electrostatic interaction with D311 of actin in the rigor conformation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This additional interaction may reduce the sliding velocity of non-muscle myosins [47]. Interestingly, the binding of myosin alters the structure of F-actin primarily at the DNase-binding loop (39-55aa) (Figure 3h), although such changes are dependent on isoforms [48]. A high-resolution structure of native vertebrate skeletal sarcomeres at different bands revealed by electron cryo-tomography shows that the two heads of double-headed myosin can interact with either a single actin filament or two separate actin filaments [49].…”
Section: How Abps Interact With Actinmentioning
confidence: 99%